Analysis of Student Ability in Professional Training Program (PTP) on Personality, Learning, Micro Teaching, and RPP Development - Sutirna Sutirna (International Journal of Learning and Instruction (IJLI), 2022)
The purpose of this study was to analyze the ability of students in implementing PTP in schools. This research method uses descriptive qualitative through a survey approach to directly pay attention to or observe students carrying out PTP activities, while the instruments used are standard assessments of personality, learning, lesson plans development, and micro teaching. The subjects of this research are PTP participants in the schools that are used as PTP locations. The results of the assessment analysis conducted by the PTP tutors and assistant lecturers found that the level of personality, learning, RPP development and micro teaching aspects of PTP participants was included in the very good category.               Keywords: Ability Analysis, PTP, Personality, Learning, RPP Development, Micro Teaching